Axial bearing capacity of socketed single cast-in-place piles - Akguner, Cem; Kirkit, Mustafa (JAPANESE GEOTECHNICAL SOC, 2012)
In this paper, a comparison is made of the axial bearing capacities estimated with pile load tests and empirical methods for seven rocksocketed single cast-in-place piles constructed in Turkey. The unconfined compressive strength of rock, obtained from pressuremeter tests, is used in the empirical correlations. It is commonly assumed that axial loads applied at the top of a socketed pile are transferred to the sides of the socket until a certain displacement is reached and that the end bearing capacity contributes only after this threshold displacement is exceeded. In practice, however, due to typically small displacements occurring in rock sockets, most, if not all, of the axial capacity is estimated to derive from the side shear. The limit displacement up to which the side frictional capacity of a socketed pile governs and the end bearing capacity starts mobilizing is examined, and no such threshold value is observed based on the findings of this study. Nevertheless, the bearing capacities obtained from the empirical correlations agree reasonably well with those calculated from pile load tests, when a systematic approach for estimating the threshold value from pile load tests is utilized and the unconfined compressive strength of socketed rocks can be estimated within reasonable accuracy applying actual field conditions. (C) 2012. The Japanese Geotechnical Society. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Base resistance; Bearing capacity; Empirical methods; Mobilization capacity; Pile load test; Side shear resistance; Socketed cast-in-place pile; Vertical load (IGC:E04/G02); LOAD-TRANSFER CHARACTERISTICS; DRILLED SHAFTS; ROUGHNESS; FRICTION; PIERS; Engineering; Geology